TANTANGAN PARA PENGAJAR DAYCARE DALAM MENGASUH ANAK USIA DINI - Muthi’ah Asholihah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
The presence of daycare can be an important solution for parents who both work to meet the needs of the family in caring for early childhood, however, caregivers and teachers in daycare face various challenges, especially in dealing with regular children and children with special needs (ABK). This study aims to analyze the challenges of daycare teachers in caring for early childhood, implementing daycare and efforts to maximize the program at Daycare Hommy Motty Karang Malang Indramayu. This study uses a qualitative method using a type of approach called qualitative descriptive through observation, interviews and documentation. Informants in this study include several informants including the daycare owner, teachers who care for and educate, and parents of students. The results of this study indicate that daycare teachers face various challenges, especially in dealing with the different moods, characters, and emotions of each child in their daily lives. However, the biggest challenge that teachers feel is when accompanying children with special needs (ABK) because it requires an extra approach and patience. Furthermore, collaboration between parents, therapists, psychologists, and teachers is a key factor in supporting optimal development. Hommy Motty Daycare only accepts children aged 1-7, so each child is individually categorized and approached differently. Toddlers aged 1-3 are included in the toddler class, while those aged 3 to 7 are included in the playgroup and kindergarten classes, focusing on various types of motor stimulation. The daycare's strengths include developing independence, creativity, communication, and socialization. Efforts to optimize the daycare program include conducting comparative studies and sharing sessions with experts from various regions and abroad, achieving an A accreditation and a ranking of 3 in West Java.